Predictive factors for invasive fungal rhinosinusitis in diabetic patients - Thwe Phyo Kan Nyunt (Chulalongkorn University, 2019)
Background: Patients with diabetes mellitus (DM) are susceptible to invasive fungal rhinosinusitis (IFRS). The mortality rate of IFRS varies greatly among the patients with DM.Objective: To identify the prognostic factors for the overall survival of patients with DM and IFRS.Methods: A retrospective study was conducted in four tertiary hospitals in Thailand, Malaysia and Myanmar. Patients diagnosed with IFRS and DM from 2008 to 2019 were identified. The outcome was the overall survival. Variables analyzed for risk factors were age, HbA1C level, ketoacidosis, white blood cell count, hyperglycemia, duration of DM, current use of diabetic medications, serum creatinine level, and the extensions of IFRS to the orbit, the cavernous sinus and intracranial cavity.Results: Sixty-five diabetic patients with IFRS (age 57.9±13.4 years, male 60%) were identified. The mortality rate was 21.5%. The extensions of IFRS to the cavernous sinus (hazard ratio 5.1, 95% CI [1.4–18.2], p=0.01) and intracranial cavity (hazard ratio 3.4, 95% CI [1.1–11.3, p=0.05) predicted mortality. Current use of diabetic medications decreased the mortality risk (hazard ratio 0.2, 95% CI [0.1–0.9], p=0.03). The 6-month overall survival of the patients with and without the cavernous sinus extension were 51.4% and 83.6%, (p <0.01), with and without intracranial extension 53.3% and 88.9%, (p<0.01), and with and without current diabetic medications 82.3% and 57.5%, respectively (p=0.05).Conclusion: The extensions of IFRS to the cavernous sinus and intracranial cavity increased the risk of death in patients with DM. Survival was primarily related to current use of diabetic medications.